2018
DOI: 10.1016/j.biopsych.2017.06.034
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Increase in Microglial RAGE Contributes to Chronic Stress–Induced Priming of Depressive-like Behavior

Abstract: Together, the results provide evidence of persistent microglial HMGB1-RAGE expression that increases vulnerability to depressive-like behaviors long after chronic stress exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
120
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(135 citation statements)
references
References 86 publications
7
120
0
1
Order By: Relevance
“…Acute stressors induce microglial activation in many brain regions [34,54], and the effects of chronic stress on microglial activation are heterogeneous due to multiple variables, including the stress paradigm (timing and types of stressors) [30,[55][56][57][58] and the age of animals [59]. Consistent with previous studies [55][56][57][58], the current study demonstrated robust and persistent effects of CUS on microglial morphology.…”
Section: Discussionsupporting
confidence: 87%
“…Acute stressors induce microglial activation in many brain regions [34,54], and the effects of chronic stress on microglial activation are heterogeneous due to multiple variables, including the stress paradigm (timing and types of stressors) [30,[55][56][57][58] and the age of animals [59]. Consistent with previous studies [55][56][57][58], the current study demonstrated robust and persistent effects of CUS on microglial morphology.…”
Section: Discussionsupporting
confidence: 87%
“…As the production of HMGB-1in the brain has been shown to be a function of age (Fonken et al, 2016), its persistent stimulation of microglia overtime is considered a risk factor for the development of neuroinflammatory pathologies and depression-like symptoms following traumatic brain injury (Fenn et al, 2014). Additionally, increased RAGE expression on microglia and microglia reactivity during periods of psychological stress mediated the induction of depressive phenotypes (Franklin et al, 2018). Other ligands of the TLR class capable of activating murine microglia and priming transcription NLRP3 include the analgesic morphine and fragments of extracellular matrix hyaluronic acid (Iyer et al, 2009).…”
Section: Priming and Activation Of The Nlrp3 Inflammasomementioning
confidence: 99%
“…Alternatively, the oxidized state of HMGB-1, designated by the formation of disulfide linkages, is capable of potentiating proinflammatory signaling as discussed above but lacks chemotactic abilities (Yang et al, 2012 ). Although the majority of studies assessing the involvement of HMGB-1 in microglial priming have come from studies using inescapable foot shock (Yang et al, 2012 ; Weber et al, 2015 ), chronic unpredictable stress (Franklin et al, 2018 ), and single prolonged stress (Lai et al, 2018 ), exposure to social stressors such as social defeat is known to enhance the intracellular concentration of reactive oxygen species (ROS; see section Oxidative Stress/Reactive Oxygen Species). Therefore, it is highly plausible that HMGB-1 may also contribute to the emergence of social stress-induced behavioral deficits.…”
Section: Sources Of Stress-induced Neuroinflammationmentioning
confidence: 99%